7 poets, 4 days, 1 book - Bell, Marvin, 1937-; Merrill, Christopher (Trinity University Press, 2009)
"The poets Marvin Bell, István László Geher, Ksenia Golubovich, Simone Inguanez, Christopher Merrill, Tomaž Šalamun, and Dean Young create a conversation in poetry that crosses linguistic borders, aesthetic boundaries, and generational divides by sharing lines to create one book"--Provided by publisher.